Glutamine repeats as polar zippers: their possible role in inherited neurodegenerative diseases. - Perutz, M F (1994)
Four inherited neurodegenerative diseases are linked to abnormally expanded repeats of glutamine residues in the affected proteins. Molecular modeling followed by optical, electron, and x-ray diffraction studies of a synthetic poly(L-glutamine) shows that it forms beta-sheets strongly held together by hydrogen bonds. Glutamine repeats may function as polar zippers, for example, by joining specific transcription factors bound to separate DNA segments. Their extension may cause disease either by increased, nonspecific affinity between such factors or by gradual precipitation of the affected proteins in neurons.